(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
In Indian Hindu mythology, the woman is said to be the better half of a man. "Shivshakti" swaroopa is Mata "Gauri", a symbol of Shakti or power. Without her, lord Shiva is assumed as incomplete. So, in this universe also without women, a society, its growth, its moral and values could not be considered as complete. The women scientists in India and abroad are fighting still for their existence and their contribution in STEM field. In the post-independence period of India, few female Physicists like "Mary Poonen Lukose", the first women of India in the field of high energy Physics at TIFR, hold the baton for survival of female Physicists in India. "Marie Curie", known as "Mother of Physics" hold the same baton for female Physicists in that time in the world and got the "Nobel Prize" in "Radioactivity” along with her husband in 1903. In this race of fight for contribution of female Physicists, the speed of Indian women Physicists was comparatively low. In this research paper, the main objectives are, understanding the position of women Physicists in India and abroad, encouraging females to explore the STEM field and the comparison of situations of the female Physicists of India and world. This paper suggests some remedial steps in this perspective along with explanation of their probable reasons. Present situation of Indian female Physicists had also been discussed in this paper. For making India as "Atmanirbhar Bharat", the role of Indian women Physicists is appreciable. Their contribution had been written now not only in India but also on the face of space.